(untitled) (Comparative & International Education Series, 2022)
Studying abroad is seen as a very beneficial aspect of any study experience. And in some countries or cultures, it is expected to be a part of the path carved by any serious potential academician. With studying abroad, and the expectations of being highly employable post one’s graduation, it can be quite a disappointment should one’s expectations of employability, and the job market not match the reality of employment within the country of origin, or the country of sojourn. This chapter intends to examine the expectations individuals have prior to graduation, the discrepancy between that and the reality of the job market, and tentative solutions to the challenges faced. Narratives from current and former international students/study "abroaders" will be included to depict the actual experiences of these individuals and how their experiences connect to the broader issue under discussion.